Academic Procrastination, Self-Efficacy, and Task Value of Pre-Service Biology Teacher During Online Learnings - Astutik, Fuji; Bukhori, Baidi; Rahmatika, Rizqi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
Academic procrastination, frequently linked to low self-efficacy and poor assignment performance, is more likely to occur when learning online. This study aims to reveal the level of academic procrastination, self-efficacy, and assignments by semester, areas of academic procrastination, and reasons for delaying assignments, as well as the relationship between academic procrastination, self-efficacy, and task value. This study uses a quantitative approach through a cross-sectional exploratory study. The sample in this study was semester 1, 3, 5, and 7 students who were taken through a stratified random sampling technique. Utilizing the survey method was the data collection methodology. The level of students is described using frequency distribution descriptive data. To use regression analysis to explain the connection between academic procrastination, self-efficacy, and task value. The reasons for procrastination were analyzed qualitatively. According to the findings, pre-service biology teachers who participated in online learning exhibited moderate levels of academic procrastination (37.8%), self-efficacy (39.1%), and task value (29.9%). More than half of the pre-service biology teachers polled stated they would prefer to postpone doing summaries of four pages of foreign language homework over twelve pages of Indonesian homework. Compared to creating a summary of the subject, more than half of biology education students said they would rather put off making a mind map. Reasons for postponing assignments varied among students. Furthermore, in academic procrastination, there is a negative simultaneous association between self-efficacy and task value.